Influence of Affective Priming Modality on Dual Mechanism of Control - Kaur, Jasnoor (My University, 2025)
The study explored how prime types, emotional valence and proportion congruency influenceDual Mechanism of Control through a spatial stroop task. The study used a within subject design, the task used 2 primes (image & words), and 3 emotional valence (happy, neutral andsad), 5proportion congruency (High LWPC, Low LWPC, Equal LWPC , High ISPC and LowISPC)and congruence (congruent & incongruent) as within subject factors. 80 participants volunteeredfor this study and they were asked to perform a spatial stroop task preceded by exposuretoemotionally valenced primes. The results found showed significant effects of prime, emotion, proportion congruence and congruence. Robust stroop effect was found as participants respondedquickly to congruent trials in comparison to incongruent trials through all conditions. Emotional valence modulated interference with neutral primes leading to faster reaction time as compared to happy primes and sad primes overall leading to delayed reaction time during incongruent trials. Effect of proportion congruency also modulated its effect in incongruent trials significantly during High ISPC, Equal LWPC and Low LWPC conditions. The finding support the DMC framework, showing how emotions and proportion effect proactive and reactive control.
Keywords: Stroop task; Cognitive Control; Affective Priming; Proportion Congruency; Emotion Regulation